PRODUKSI WATER KEFIR GULA AREN - Annisa Muntaz, Mahardhani
Water kefir is a probiotic drink made from fermented sucrose solution by water kefir grains. This drink can be consumed by vegans and people with lactose allergies conditions. Water kefir fermentation produces bioactive compounds that have antimicrobial activity. In this study, palm sugar was used as a substrate for water kefir fermentation. The composition of bioactive compounds and organoleptic characteristics of water kefir were influenced by the amount of grains inoculum, sugar concentration, and fermentation time. Therefore, this study aims to: (1) optimize the sugar concentration (5%, 7.5%, 10% (w/v)) to produce palm sugar water kefir; (2) determine the changes of microbial diversity that are involved in the production of palm sugar water kefir using optimum sugar concentration; (3) determine the antimicrobial production of palm sugar water kefir using optimum sugar concentration. Organoleptic tests were carried out by 20 untrained panelists based on parameters of taste (sweet, sour, bitter), aroma (sour and alcoholic), soda sensation, color, texture, and overall preference. Microbial diversity analysis was performed on the growth medium of NA, MRSA, PDA, and GYCA. Isolation and identification of microbes was carried out based on 16s rRNA or ITS sequences. Analysis of acid and sugar concentrations was carried out using the HPLC method. Analysis of antimicrobial activity was carried out using the Kirby-Bauer disk diffusion method against 3 test bacteria with a cell density of 106 CFU/mL on NA medium. From the results of the study, the best sugar concentration to produce palm sugar water kefir was 10% (w/v) with the highest organoleptic index of 3.9 ± 0.0 (scale 5) at 18 hours of fermentation. Based on the analysis of microbial diversity using 10% (w/v) sugar concentration, 10% (w/v) inoculum concentration, at 25oC incubation temperature, the results showed that the group of lactic acid bacteria (LAB) dominated (108 CFU/mL), followed by yeast (107 CFU/mL) then acetic acid bacteria (106 – 107 CFU/mL) throughout the fermentation process. These three types of microbes can use sucrose substrate simultaneously; LAB produces dextran and fructose, while yeast and BAA produce glucose and fructose which will be fermented by LAB and BAA into acid. The dominant LAB isolate was Schleiferilactobacillus harbinensis, the dominant yeast isolate was Saccharomyces cerevisiae, and the dominant BAA isolate was Acetobacter pasteurianus. The highest antimicrobial activity was produced in palm sugar water kefir fermented for 36 hours (pH 3.24) with inhibition zone diameters of 2 ± 0.0 mm against Bacillus cereus, 3 ± 1.4 mm against Staphylococcus aureus, and 2 ± 0.0 mm against Escherichia coli.